Transperitoneal Nephrectomy of Hydronephrotic Tubercular Kidney: A Rare Case Report - Sunder Goyal; Rajesh Aggarwal; Paramjeet Singh (Archives of Clinical and Experimental Surgery, 2014)
Genitourinary tuberculosis (GUTB) is the second most common form of extrapulmonary tuberculosis, with more than 90% of cases occurring in developing countries. As tuberculosis causes complete destruction of the kidney, the giant hydronephrosis, due to tuberculosis, is a rare condition. Although the role of surgery in GUTB has decreased since the advent of anti-TB therapy, it can still have a role as an adjunct to drug treatment. A 65-year-old male presented with a huge abdomen. Clinical diagnosis of congenital pelvi-ureteric junction (PUJ) obstruction was made, and percutaneous nephrostomy was done to save the function of the kidney. Ultrasound and computed tomography (CT) confirmed the diagnosis. As it turned out to be a nonfunctioning kidney, transperitoneal laparoscopic nephrectomy was done. A histopathological report of the removed kidney revealed renal tuberculosis. Tubercular PUJ stricture presenting as giant hydronephrosis is uncommon; we thus present this case. [Arch Clin Exp Surg 2014; 3(2.000): 118-122]